2012
DOI: 10.1038/nature10930
|View full text |Cite
|
Sign up to set email alerts
|

Coherent quantum phase slip

Abstract: A hundred years after discovery of superconductivity, one fundamental prediction of the theory, the coherent quantum phase slip (CQPS), has not been observed. CQPS is a phenomenon exactly dual1 to the Josephson effect: whilst the latter is a coherent transfer of charges between superconducting contacts 2,3 , the former is a

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
299
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(314 citation statements)
references
References 33 publications
8
299
2
1
Order By: Relevance
“…An apparent observation of a coherent phase slip in a conducting weak link 19 may be viewed as an incipient experimental step in that direction. That makes the question about the intrinsic mechanisms of decoherence in weak links important.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…An apparent observation of a coherent phase slip in a conducting weak link 19 may be viewed as an incipient experimental step in that direction. That makes the question about the intrinsic mechanisms of decoherence in weak links important.…”
Section: Pacs Numbersmentioning
confidence: 99%
“…Hence, it is quite realistic to fabricate and study quasi-one dimensional (1D) superconducting systems [1]. It has been demonstrated that in such objects quantum fluctuations of the phase of the complex order parameter e i can suppress zero resistivity at temperatures well below the critical point T<<T c [2][3][4][5][6][7] and dramatically modify the current-phase relation and the magnitude of persistent currents in narrow superconducting nanorings [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…2,13 Ultranarrow nanowires have been developed in both these materials with effective diameters in the range 20-40 nm. [14][15][16] QPS in InO x has been demonstrated via spectroscopic measurements of E S in a QPS qubit, 2 while alternative evidence for QPS (in fact, for the dual effect of coherent tunneling of single Cooper pairs) has been observed in NbSi nanowires via quantum interference in a device dual to the SQUID consisting of two QPSJs joined by a superconducting island. 15 Preliminary signs of QPS 17,18 and of dual Shapiro steps 19 have been observed in a Ti nanowire, but only traces of steps are observed.…”
Section: Introductionmentioning
confidence: 99%